2021
DOI: 10.3892/ijmm.2021.4970
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA XIST inhibits osteoblast differentiation and promotes osteoporosis via Nrf2 hyperactivation by targeting CUL3

Abstract: Osteoporosis (OP) is a common skeletal disorder characterized by a low bone mass and the deterioration of bone structure. Long non-coding (lnc)RNA X inactive-specific transcript (XIST) is highly expressed in the serum and monocytes of patients with OP. Thus, the purpose of the present study was to explore the mechanisms underlying the role of XIST in the progression of OP. To establish animal models of OP, female rats underwent a bilateral ovariectomy. The bone mineral density of individual rats was measured u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…EGR1 [92], ATF3 [93], XIST (X inactive specific transcript) [94], S100A12 [95] and S100A8 [96] were identified as a candidate genes of heart problems. EGR1 [97], ATF3 [63] and XIST (X inactive specific transcript) [98] are involved in the development of osteoporosis. A recent research suggested that EGR1 [99] and S100A8 [100] contributed to the advancement of depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…EGR1 [92], ATF3 [93], XIST (X inactive specific transcript) [94], S100A12 [95] and S100A8 [96] were identified as a candidate genes of heart problems. EGR1 [97], ATF3 [63] and XIST (X inactive specific transcript) [98] are involved in the development of osteoporosis. A recent research suggested that EGR1 [99] and S100A8 [100] contributed to the advancement of depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies have confirmed that RBM15 in stress hematopoiesis have a variety of aging-related physiologic changes, including increased DNA damage and NF-κB activation ( 53 ), which may serve as important pathological factors in the development of osteoporosis. In addition, study has reported that knockdown of RBM15 and RBM15B impairs XIST-mediated gene silencing ( 52 ), which influences osteoblast differentiation in osteoporosis ( 54 ). Therefore, to our knowledge, the seven candidate m6A modulators may play an important part in the occurrence and development of osteoporosis according to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that the activation of Nrf2 promotes osteogenic differentiation by increasing heme oxygenase-1 (HO-1) expression ( Liu et al, 2018 ; Chen et al, 2020b ). However, it is worth noting that the overexpression of Nrf2 might inhibit the differentiation of osteoblasts ( Chen et al, 2021b ). GSH inhibits the osteoclast differentiation-mediated NF-κB signaling pathway induced by ROS ( Han et al, 2020 ).…”
Section: Antioxidant Substancesmentioning
confidence: 99%